Can seagrass modify the effects of ocean acidification on oysters?. (April 2022) - Garner, Natasha; Ross, Pauline M.; Falkenberg, Laura J.; Seymour, Justin R.; Siboni, Nachshon; Scanes, Elliot
Abstract: Solutions are being sought to ameliorate the impacts of anthropogenic climate change. Seagrass may be a solution to provide refugia from climate change for marine organisms. This study aimed to determine if the seagrass Zostera muelleri sub spp. capricorni benefits the Sydney rock oyster Saccostrea glomerata, and if these benefits can modify any anticipated negative impacts of ocean acidification. Future and ambient ocean acidification conditions were simulated in 52 L mesocosms at control (381 μatm) and elevated (848 μatm) CO2 with and without Z. muelleri . Oyster growth, physiology and microbiomes of oysters and seagrass were measured. Seagrass was beneficial to oyster growth at ambient p CO2, but did not positively modify the impacts of ocean acidification on oysters at elevated p CO2 . Oyster microbiomes were altered by the presence of seagrass but not by elevated p CO2 . Our results indicate seagrasses may not be a panacea for the impacts of climate change. Highlights: Effect of seagrass on oyster shell growth and extracellular pH at ambient p CO2 No effects of seagrass on oyster growth or extracellular pH at elevated p CO2 Microbiome of oysters was not affected by elevated p CO2 . Microbiome of seagrass was altered by elevated p CO2 . Seagrass may not modify the impacts of climate change.